GAYA BAHASA SINDIRAN PADA BAHASA IKLAN PENYEDIA LAYANAN JARINGAN TELEPON - Prameswari, Jatut Yoga (STKIP PGRI Bandar Lampung, 2019)
Language as a communication tool is the most effective way of conveying messages. Language is what will give a lot of influence to the recipients of the message. This influence is what will benefit the language users. Among them, telephone network service providers who are competent as creative as possible in making their advertising language. In the use of this ad language, of course there is a style of language. Satire language style is more often heard in the use of advertising languages. This is done so that consumers are quickly attracted to and affected by their products. The satire language style consists of five categories, namely; irony, sarcasm, cynicism, antifrasis, inuendo. this study uses descriptive qualitative research methods. Research instruments, namely video ad network telephone service providers, such as Telkomsel, Indosat, XL, and Axis are the subjects of this study. Notes, recording devices using smart phones, etc. are used as instruments in this study. The results of advertising analysis of telephone network service providers, namely in the operator irony category XL obtained the highest number of 15%. The highest category of sarcasm is 14%, cynicism is 12%, and inuendo 5% is obtained by Indosat operators. Thus, it can be concluded that in each video ad network service providers contain satirical language styles and this phenomenon can be explained in terms of language